11(4-66x)+5(13x+1)=9

Simple and best practice solution for 11(4-66x)+5(13x+1)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(4-66x)+5(13x+1)=9 equation:



11(4-66x)+5(13x+1)=9
We move all terms to the left:
11(4-66x)+5(13x+1)-(9)=0
We add all the numbers together, and all the variables
11(-66x+4)+5(13x+1)-9=0
We multiply parentheses
-726x+65x+44+5-9=0
We add all the numbers together, and all the variables
-661x+40=0
We move all terms containing x to the left, all other terms to the right
-661x=-40
x=-40/-661
x=40/661

See similar equations:

| 2/3(3z-15)=22 | | 2^x+3+2^-x=6 | | 3y+5=y+75 | | 13j=184 | | -98+6x=28-3x | | 5n+3=213 | | 6-r=2 | | 38.02+.25m=110 | | 2x^2+6+x=2x^2+2+2x | | 10y-4(y+2)=-20 | | 0=2x3-5x2 | | -2(n-2)+6(n+7)=74 | | 1/3(6x+-3)=9 | | -10=-8+k | | -2/3(15c-24)=4/9(18-27c) | | 13-5x=5x+13 | | 7s=32 | | 3x+10-x-5=2x-5 | | 7x+5(5x+3)=-241 | | t-17=16 | | 2.7r+5.3(7.552r+.2)=-3.54256-3.3r | | -3x+33=-21+6x | | C=81+7h | | 12y+30=168 | | 1/2x+4=x-2 | | 576x^2-441=0 | | 2/5y+1/2=5/2 | | z/5-4=3/4 | | X^2-7x+23=0 | | 9t-4t-4t=20 | | 1/6x=21/3 | | 16x+21=1x |

Equations solver categories